2007
DOI: 10.1111/j.1365-2389.2007.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the 2,4‐dichlorophenoxyacetic acid herbicide with soil organic matter moieties: a theoretical study

Abstract: The determination of the structure of humic substances from soils and natural waters is an intriguing problem in soil science. Humic substances consist of molecules covering a broad distribution of molecular size and involving different functional groups. Taking this into account, we have chosen smaller model systems with functional groups typically present in humic substances. We investigated theoretically, by quantum chemical calculations, the environmental effects on the complexes formed from the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 46 publications
0
41
0
1
Order By: Relevance
“…Previous simulation studies of the binding of organic contaminants by NOM [25][26][27][28][29], however, often have had limitations that impede realistic characterization of antibiotic-NOM interactions. These limitations include systems studied in vacuo [26,28] or under low hydration [25,27] and restriction to fully protonated NOM [26,27,29]. Furthermore, conformational changes in NOM following adsorption of an organic contaminant are expected [26], but these structural rearrangements and their implications for adsorption have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous simulation studies of the binding of organic contaminants by NOM [25][26][27][28][29], however, often have had limitations that impede realistic characterization of antibiotic-NOM interactions. These limitations include systems studied in vacuo [26,28] or under low hydration [25,27] and restriction to fully protonated NOM [26,27,29]. Furthermore, conformational changes in NOM following adsorption of an organic contaminant are expected [26], but these structural rearrangements and their implications for adsorption have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There also exists a large literature on sorption studies conducted with natural minerals and other geosorbents, like sediments or soils, with varying organic matter content [88][89][90][91][92][93][94][95][96][97][98][99][100][101]. For example, the interaction between the (110) goethite surface and acetic acid, acetate, 2,4-dichlorophenoxyacetic acid, 2,4-dichlorophenoxyacetate and benzene have been studied by means of quantum mechanical calculations using the B3LYP approach [88], whereas the interaction of esters and acids with iron oxide surfaces has also been reported [47,89].…”
Section: Introductionmentioning
confidence: 99%
“…This strong reduction is due to the loss of solvent accessibility to the polar surface area of the complexes in comparison to the isolated reactants whose polar functional groups are available for interaction with the polar solvent. This effect was investigated in detail for various hydrogen-bonded complexes in our previous work (Aquino et al 2002) and also shown in our paper on complexes of 2,4-dichloro-phenoxyacetic acid (2,4-D; Aquino et al 2007). Thermal effects and entropy changes in solution were taken from the gas phase calculations according to Eqs.…”
Section: Molecular Modelingmentioning
confidence: 90%
“…11. This model was applied in our study of the 2,4-D complexes (Aquino et al 2007) and most recently for acrylic acid complexes (Aquino et al 2008). The results of the combined micro + global solvation approach can be considered as the most complete description of the complex formation reactions in solution.…”
Section: Molecular Modelingmentioning
confidence: 99%
See 1 more Smart Citation